2021
DOI: 10.1177/13506501211070654
|View full text |Cite
|
Sign up to set email alerts
|

Review of the coatings used for brake discs regarding their wear resistance and environmental effect

Abstract: Wear of a friction pair of brake (brake disc and pads), in addition to reducing the active safety of vehicles, leads to the formation of particles that can affect the environment and human health. In addition to the technologies that are being developed for the collection of particles created by the wear of brakes during braking process, today new materials are being introduced, as well as various technologies for processing friction pairs with the aim of reducing brake wear and thus the formation of particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…With regard to the tribological system as a whole, however, the mere coating of brake discs does not automatically guarantee high particulate reduction potential. Rather, the process parameters must be mastered in the fabrication of the coating surface and brake linings specially adapted to the requirements of the coating must be used [10,41]. In general, the compatibility of the friction partners is decisive for performance and emission characteristics as well as for comfort aspects and the durability of the braking system [35].…”
Section: Influence Of Alternative Brake Disc Materialsmentioning
confidence: 99%
“…With regard to the tribological system as a whole, however, the mere coating of brake discs does not automatically guarantee high particulate reduction potential. Rather, the process parameters must be mastered in the fabrication of the coating surface and brake linings specially adapted to the requirements of the coating must be used [10,41]. In general, the compatibility of the friction partners is decisive for performance and emission characteristics as well as for comfort aspects and the durability of the braking system [35].…”
Section: Influence Of Alternative Brake Disc Materialsmentioning
confidence: 99%
“…It was found that depending on the disc material, the temperature has a different effect on the resulting particle emission. The importance of disc coating in order to reduce the emission of particles generated in the braking process and to reduce the intensity of wear was presented in research [37]. In this research, it was shown that different materials can be used to cover the surface of the brake discs, as well as technologies that can reduce the intensity of brake wear and the resulting emission of particles.…”
Section: Research Resultsmentioning
confidence: 99%
“…The friction coefficient (FC), wear rate (WR) and weight loss (WL) are the criteria to measure their performance (Bijwe, 1997;Mann et al, 2021). The wear generated due to braking may produce particles, which constitute the primary components of particulate matter in the air (Vasiljevic et al, 2022(Vasiljevic et al, , 2023. During the braking process, the friction performance is subject to a comprehensive influence from various factors, including but not limited to, production method, surface roughness and contact load value.…”
Section: Introductionmentioning
confidence: 99%